Gesù e la Samaritana (Gv 4) nell’interpretazione di Agostino - Caruso OSA, Giuseppe (Alpha Omega, 2010)
Augustine commented twice on the text of the Samaritan women in Jn 4; the first time was in the Quaestio 64 of De diversis quaestionibus octogintatribus, and again in his commentary of St. John’s gospel. Betweeen these two Augustinian exegesis there are, of course, many similarities and some differences. This paper analyzes both in search of a greater unterstanding of the Augustine’s exegetical method and results.